Donepezil and cognitive remediation therapy to augment treatment of alcohol use disorder related mild cognitive impairment (AUD-MCI): An open label pilot study with historical controls. Issue 4 (October 2021) - Bell, Morris D.; Pittman, Brian; Petrakis, Ismene; Yoon, Gihyun
Background: Pharmacological and psychosocial interventions have only modest efficacy for Alcohol Use Disorder (AUD), and continued alcohol use has brain effects on neurocognition, which place heavy drinkers at increased risk of early onset dementia. The most common neurocognitive deficits are in the domains of executive function and memory, and these deficits may impact AUD treatment outcomes. AUD related Mild Cognitive Impairment (AUD-MCI) is a diagnosis in DSM-V and ICD-10. Donepezil, a cholinesterase inhibitor, is currently FDA approved for treatment of dementia, and recent preclinical research suggests anticholinesterase agents may treat alcoholism. Another approach to cognitive recovery is Cognitive Remediation Therapy (CRT). Recent research supports CRT efficacy in schizophrenia and related disorders, and some research suggests that CRT could improve neurocognition in substance abuse disorders (SUDs). This is the first report of an open-label clinical trial that combined donepezil with CRT to improve neurocognitive and clinical outcomes in the early phase of AUD recovery. Methods: Eleven older male US Veterans with AUD-MCI as determined by Level II neurocognitive criteria and who had recently relapsed participated in an open-label trial of 13 weeks of donepezil combined with CRT. They were compared with matched historical control samples on neurocognitive and clinical outcomes. Results: Participants had excellent adherence to donepezil and CRT. Neurocognitive improvements were highly significant on a composite score of learning and memory and executive function measures ( p < .0001) and was significantly better than historical matched controls ( p < .001). On a Clinical Global Impression scale, 90.9% of participants had a good clinical recovery compared with 59.5% of historical matched controls ( p <.052). Conclusions: AUD-MCI has not received much research attention but is of considerable public health importance. Findings in this open-label trial of donepezil + CRT should encourage further investigation into the clinical benefit of this combined treatment for AUD-MCI.